Acquisitions versus licensing agreements as vehicles for technology transfer. (28th January 2010) - Forsans, Nicolas; Balasubramanyam, V.N.
Traditionally, emerging economies have sought to acquire technology and know-how from inward FDI and/or technology licensing agreements. In the recent past, countries such as India and Brazil followed the lead of Japan and resorted to technology licensing agreements in a major way for their requirements of technology and know-how. In recent years, several emerging economies, with India and China being the most prominent, have acquired foreign firms with acquisition of technology and know-how as one of the principal motives for such overseas investments. This paper argues that such overseas acquisitions are a much more efficient and inexpensive source of technology and know-how for countries such as India than licensing agreements.